Perencanaan Kanban Card Controller (KCC) dalam Pengendalian Tingkat Produksi Guna Meminimalisasi Kekurangan dan Kelebihan Produksi - Annisa Kesy Garside (Jurnal Teknik Industri, 2000)
This  research  has  aim to plan  Kanban  Control  Card  (KCC)  in production   rate  controlling some  products  as:  Office  Table  (MTK),   Tower  Chest  Four  Flours  (TC-4),Tower    Chest  Six Flours (TC-6),   Simple Table  (MD).In this  research  we  need  data  such as  :   production   demand  data  history, production   lead time,   demand   forecasting   and  production   data  base  from demand  history   (  25  weekly  periodic), then  forecast   demand  in periodic  26 tli   using  Time  series  method  with  Trend  Analysis   in  a second periodic.Using  MRP  logic,  forecasting   result  account  to  result  Planed  Order  Release (PORs)  for each work  station.  From  the data analysis  can be found  :      the number  ofKanban    Card in each work station  of  production   devision    and the  second  is  less  maximum   inventory   value  than    inventory value using  MRP,  so TIT is  proved  not efective  in a fluctuative   production  rate.